2019
DOI: 10.20965/jrm.2019.p0427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Task Achievement of Robotics Programming Based on Image Information

Abstract: It is difficult to make an evaluation based solely on whether programming has been achieved. However, appropriate evaluation according to the achievement level leads to learners’ subjective programming learning, and to learning support that corresponds to individuals. Therefore, the quantitative evaluation of programming learning is as important as teaching and educational methods. Since programming education is being introduced to elementary and junior high schools, a programming evaluation method for this ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The use of robotics systems in programming courses has also shown that it can enhance the coding skill of students and inculcate computational thinking among them [16][17][18]. A robot platform was used in [19] to increase the ability of electronic engineering undergraduate students to build algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of robotics systems in programming courses has also shown that it can enhance the coding skill of students and inculcate computational thinking among them [16][17][18]. A robot platform was used in [19] to increase the ability of electronic engineering undergraduate students to build algorithms.…”
Section: Introductionmentioning
confidence: 99%